Economic impact of pharmaceutical interventions on healthcare services from Brazil: a systematic review - Gustavo B. TIGUMAN; Ronaldo M. JUNIOR (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: The aim of this research was to systematically review the studies that investigated the economic impact of the pharmaceutical intervention in Brazilian healthcare services. Methods: A systematic search was conducted in the MEDLINE, EMBASE, and LILACS databases to select the economic evaluations published until November 2019. Two independent authors selected the studies, extracted the data, and assessed the methodological quality using the 19-items Consensus on Health Economic Criteria (CHEC-list) instrument and the reporting quality using the 24-items Consolidated Standards of Economic Health Assessment (CHEERS) checklist. Results: Out of the 290 identified articles, 10 met the eligibility criteria. Most studies were conducted in the southeastern region of Brazil (n=7) and significantly differed in design, economic outcome measure, and type of intervention. The majority (n=8) reported that pharmaceutical practice resulted in reduction of costs and clinical benefits to patients. In general, the methodological and the reporting qualities of the studies were low/moderate with an average score at CHEC-list of 10.3 (range: 3-16 points) and at CHEERS of 15.8 (range: 11-21 points). Conclusions: The Brazilian studies indicate that the pharmacist intervention can lead to economic and clinical benefits for healthcare services. The methodological and the reporting qualities of the studies were limiting factors.